2020
DOI: 10.3390/antibiotics9070425
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Carbapenem-Resistance Genes in Klebsiella Species Recovered from Selected Environmental Niches in the Eastern Cape Province, South Africa

Abstract: Carbapenemase-producing Enterobacteriaceae (CPE) have been heavily linked to hospital acquired infections (HAI) thereby leading to futility of antibiotics in treating infections and this have complicated public health problems. There is little knowledge about carbapenemase-producing Klebsiella spp. (CPK) in South Africa. This study aimed at determining the occurrence of CPK in different samples collected from selected environmental niches (hospitals, wastewater treatment plants, rivers, farms) in three distric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
3
13
1
Order By: Relevance
“…Such resistant phenotypes indicate antibiotic failure, should these members of antibiotics be used in the treatment of any disease case implicated by any of the characterized members of organisms. Similar resistant phenotypes have been previously reported by 2 , 3 , 9 amongst some enteric associated bacterial pathogens, which show a failure of the various antibiotic regimen used, thereby arousing the need for effective alternative antibiotics. The antibacterial signatures also yielded multiple antibiotic-resistant phenotypes (MARP) with a profile of antibiotic resistance numbers ranging from 4 to 8 and multiple antibiotic-resistant indexes (MARI) range 0.4 to 0.7.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Such resistant phenotypes indicate antibiotic failure, should these members of antibiotics be used in the treatment of any disease case implicated by any of the characterized members of organisms. Similar resistant phenotypes have been previously reported by 2 , 3 , 9 amongst some enteric associated bacterial pathogens, which show a failure of the various antibiotic regimen used, thereby arousing the need for effective alternative antibiotics. The antibacterial signatures also yielded multiple antibiotic-resistant phenotypes (MARP) with a profile of antibiotic resistance numbers ranging from 4 to 8 and multiple antibiotic-resistant indexes (MARI) range 0.4 to 0.7.…”
Section: Discussionsupporting
confidence: 79%
“…Primary infections associated with the aforementioned bacterial pathogens have remained a public health concern due to the multiple antibiotic resistance (MAR) revealed in the studies of various investigators. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with those of previous studies testing the antimicrobial resistance in Klebsiella isolates recovered from wastewaters. They were defined as MDR, being resistant to almost all tested antimicrobial agents [ 10 , 17 , 40 ]. Besides the resistance to all penicillins, beta-lactamase inhibitors, non-extended spectrum cephalosporins (1st and 2nd generation), extended-spectrum cephalosporins (3rd and 4th generation), broad-spectrum cephalosporins (5th generation), carbapenems, monobactams, fluoroquinolones, we encountered a high percentage (73%) of resistance to tigecycline (TGC).…”
Section: Resultsmentioning
confidence: 99%
“…The dissemination of antibiotic resistance genes (ARGs) worldwide, especially the carbapenemase family (CRG), became an urgent global health threat [ 9 , 10 ], mostly because their presence was detected in both clinical and environmental settings [ 11 ]. Wastewaters represent a hotspot for the development and dissemination of AMR and ARGs [ 12 ], being a key factor in this process [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, monitoring the antibiotic resistance level trends in the community using WBE methods cannot provide information about the nonhuman sources of bacteria and genes. Some authors have shown that livestock, slaughterhouses, domestic pets, food waste ( 69 ), wildlife, and animal farms sewage can contain carbapenem-resistant bacteria and CRGs ( 70 ), but not in significant amounts. For example, Europe registered a prevalence of <1% carbapenem-resistant Enterobacteriaceae among livestock and pets ( 71 ).…”
Section: Resultsmentioning
confidence: 99%